Avaliação da formação continuada da área de Matemática do PNAIC no Município de Ivaiporã: a percepção dos professores egressos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This research aimed to analyze how the literacy teachers who participated in the National Pact for Literacy at the Right Age (Pacto Nacional pela Alfabetização na Idade Certa – PNAIC) evaluate the continuing education in Mathematics carried out in 2014, in the municipality of Ivaiporã, Paraná, Brazil, in 2014.The research with a qualitative approach is of the evaluative case study type and had as subjects the teachers who participated in the Program. The procedures for data production were: documentary analysis, questionnaire with open and closed questions and semi-structured interviews. The methodology adopted for the analysis of the data produced in the set of questionnaires and interviews was in combination with the use of the Discursive Textual Analysis (ATD) methodology, by Moraes and Galiazzi (2007), and the textual analysis report called Descending Hierarchical Classification (DHC) generated by the Iramuteq software. The discussion and analysis of empirical data were conducted at the end of the interviews, supported by the theoretical-methodological framework of the evaluation of educational policies and programs, teacher training, literacy and mathematical literacy and the game and play methodology. The results of the analysis of the evaluation of continuing education in Mathematics revealed the perception of the participating literacy teachers, who highlighted that: the training received provided moments of reflection and exchanges of experiences that contributed to qualification and professional development of teachers; the game and play strategy contributes to facilitate the teaching and learning processes of mathematical content for literacy classes; the financial incentive received in the form of monthly scholarships during the training was characterized as a form of professional valorization to literacy teachers; reflections on teaching and learning during training contributed to teachers making a self-analysis of their teaching practices, triggering changes in their pedagogical practices; the theory-practice relationship was realized in the study of notebooks and in moments of discussion, planning and development of activities in schools and exchange of experiences among the participating teachers. The teachers understood the objectives of the PNAIC for teacher training, as well as the importance of participation for their professional improvement and possible improvements in teaching practices. Finally, they expressed the desire for continuity of the PNAIC, or continuing education programs in Mathematics with similar proposals for teachers who work in literacy classes.
Keywords: Alfabetização Matemática; Anos iniciais do Ensino Fundamental; Avaliação de políticas e programas educacionais; Formação continuada de professores alfabetizadores; PNAIC; Mathematical Literacy; Early grades of Elementary School; Evaluation of educational policies and programs; Continuing Education of literacy teachers; PNAIC; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA